A Bi-doped Li3V2(PO4)3/C cathode material with an enhanced high-rate capacity and long cycle stability for lithium ion batteries. Issue 40 (22nd September 2015) - Cheng, Yi; Feng, Kai; Zhou, Wei; Zhang, Hongzhang; Li, Xianfeng; Zhang, Huamin
Abstract : A promising cathode material Li3 V1.97 Bi0.03 (PO4 )3 /C for high-power Li rechargeable batteries shows excellent electrochemical performance. Abstract : Bi-doped compounds Li3 V2− x Bi x (PO4 )3 /C ( x = 0, 0.01, 0.03, 0.05, 0.07) are prepared by a sol–gel method. The effects of Bi doping on the physical and electrochemical properties of Li3 V2 (PO4 )3 are investigated. X-ray diffraction (XRD) analysis indicates that Bi doping does not change the monoclinic structure of Li3 V2 (PO4 )3 . A detailed analysis of the XRD patterns suggests that Bi 3+ ions partly enter into the crystal structure of Li3 V2 (PO4 )3 and enlarge the lattice volume of Li3 V2 (PO4 )3 . According to the results of cycle and rate performance measurements, moderate Bi 3+ doping is beneficial in improving the electrochemical properties of Li3 V2 (PO4 )3 . Among all the samples, Li3 V1.97 Bi0.03 (PO4 )3 /C shows the best cycle and rate performance. At 3.0–4.3 V, the initial discharge capacity of Li3 V1.97 Bi0.03 (PO4 )3 /C is as high as 130 mA h g −1, close to the theoretical specific capacity of 133 mA h g −1 . The capacity retention of Li3 V1.97 Bi0.03 (PO4 )3 /C is almost 100% after 100 cycles at 3.0–4.3 V. In addition, Li3 V1.97 Bi0.03 (PO4 )3 /C exhibits excellent low-temperature and high-rate performance. Impedance spectroscopy (EIS) and cyclic voltammetry (CV) curves indicate lower charge transfer resistance and a larger Li ion diffusion rate of Li3 V1.97 Bi0.03 (PO4 )3 /C than the primary Li3 V2 (PO4 )3 /C. The excellent electrochemical performance of Li3 V1.97 Bi0.03 (PO4 )3 /C can be attributed to its larger Li ion diffusion channels, higher electronic conductivity, higher structural stability and smaller particle size.